Влияние схемы расположения компонентов реакционной шихты на характеристики синтезируемых кристаллов кубического нитрида бора - Боримский, И.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The comparative analysis of characteristics of the cubic boron nitride crystals, gained at a synthesis with application of the homogeneous and level-by-level arrangement of the reaction mixture components was carried out. It was shown, that at the homogeneous arrangement of a reaction mixture components the weight of crystals gained at every working cycle increases and their isomerizes is raised.